Grodzisko z wczesnej epoki żelaza w Rogaczewie Wielkim, gm. Krzywiń, pow. kościański (stan. 22, AZP 60-27/129). Wyniki wstępnych badań weryfikacyjnych 223 - Krzepkowski, Marcin; Szczurek, Grzegorz; Golis, Artur; Rybicki, Robert (Folia Praehistorica Posnaniensia, 2024)
This paper discusses the preliminary results of research on a newly discovered Early Iron Age defensive structure in southern Wielkopolska [Great Poland]. So far, the scope of work on the site at Rogaczewo Wielkie, Kościan District, has been limited to a comprehensive analysis of archival material, LiDAR data, surface research and a small survey trench. The obtained results of radiocarbon dating make it possible to include the Rogaczewo settlement in the catalogue of Wielkopolska fortified settlements of the Hallstatt period. The research, which will be continued, provide an excellent example of model cooperation between archaeological circles and institutions and enthusiasts who are not professionally involved in the protection of archaeological cultural heritage.